The impact of e-cigarette product place in music videos on susceptibility to use e-cigarettes among young adults: An experimental investigation. (July 2022) - Donaldson, Scott I.; Dormanesh, Allison; Escobedo, Patricia; Majmundar, Anuja; Kirkpatrick, Matthew; Allem, Jon-Patrick
Highlights: Product placement in music videos is a growing promotional strategy. This experiment exposed participants to e-cigarette product placement. E-cigarette product placement in music videos impacted e-cigarette susceptibility. Young adults who have never used e-cigarettes may be vulnerable to these promotions. Abstract: Introduction: Product placement in music videos is a growing promotional strategy. This study examined the impact of e-cigarette product placement and imagery in music videos on susceptibility to use e-cigarettes among young adults. Methods: A non-probability sample of young adults (18 to 24) in Southern California were recruited to participate in an experiment over Zoom. Participants were randomized into a treatment or a control group. The treatment group watched seven music videos with e-cigarette product placement and imagery. The control group watched the same seven music videos with all e-cigarette product placement and imagery digitally removed. Participants completed a questionnaire after watching the music videos. The focus of the analysis was on susceptibility to use e-cigarettes in the future among never users ( n  = 303). Results: Participants in the treatment group who had never used e-cigarettes were more likely to report intentions to try e-cigarettes in the future ( OR  = 1.94, 95% CI [1.08, 3.54], compared to participants in the control group. Participants in the treatment group who had never used e-cigarettes were more likely to report peer influence ( OR  = 1.97, 95% CI [1.19, 3.32], compared to participants in the control group. While these subitems of susceptibility to use e-cigarettes were statistically significant, the relationship between the treatment group and the composite measure of susceptibility was not. Conclusion: Exposure to e-cigarette product placement in music videos may increase young adults' intentions to try e-cigarettes in the future. Federal, state, and local tobacco control regulatory bodies should consider strategies to reduce e-cigarette product placement in music videos.